Sexual Rehabilitation After Treatment for Prostate Cancer—Part 1: Recommendations From the Fourth International Consultation for Sexual Medicine (ICSM 2015). Issue 3 (1st March 2017) - Salonia, Andrea; Adaikan, Ganesh; Buvat, Jacques; Carrier, Serge; El-Meliegy, Amr; Hatzimouratidis, Kostas; McCullough, Andrew; Morgentaler, Abraham; Torres, Luiz Otavio; Khera, Mohit
Abstract: Introduction: Sexual dysfunction is common in patients after radical prostatectomy (RP) for prostate cancer. Aim: To provide the International Consultation for Sexual Medicine (ICSM) 2015 recommendations concerning prevention and management strategies for post-RP erectile function impairment in terms of preoperative patient characteristics and intraoperative factors that could influence erectile function recovery. Methods: A literature search was performed using Google and PubMed databases for English-language original and review articles published up to August 2016. Main Outcome Measures: Levels of evidence (LEs) and grades of recommendations (GRs) based on a thorough analysis of the literature and committee consensus. Results: Nine recommendations are provided by the ICSM 2015 committee on sexual rehabilitation after RP. Recommendation 1 states that clinicians should discuss the occurrence of postsurgical erectile dysfunction (temporary or permanent) with every candidate for RP (expert opinion, clinical principle). Recommendation 2 states that validated instruments for assessing erectile function recovery such as the International Index of Erectile Function and Expanded Prostate Cancer Index Composite questionnaires are available to monitor EF recovery after RP (LE = 1, GR = A). Recommendation 3 states there is insufficient evidence that a specific surgical technique (open vs laparoscopic vs robot-assisted radical prostatectomy) promotes better results in postoperative EF recovery (LE = 2, GR = C). Recommendation 4 states that recognized predictors of EF recovery include but are not limited to younger age, preoperative EF, and bilateral nerve-sparing surgery (LE = 2, GR = B). Recommendation 5 states that patients should be informed about key elements of the pathophysiology of postoperative erectile dysfunction, such as nerve injury and cavernous venous leak (expert opinion, clinical principle). Conclusions: This article discusses Recommendations 1 to 5 of the ICSM 2015 committee on sexual rehabilitation after RP.